SERVICE QUALITY OF LAND CERTIFICATE AT LAND OFFICE OF PALEMBANG-INDONESIA: SERVQUAL MODEL - Hardiyansyah - Hardiyansyah (NATAPRAJA, 2018)
ABSTRACTThe purpose of this research was to find out and analyze the quality of land certificate service at Land Office of Palembang. This research was a type of quantitative descriptive research. This study focused on presenting data and facts, not hypothesis or prediction statements. The samples of the research were 50 respondents who were registering their land certificates. Based on the results of research and discussion, it found that the overall quality of services provided by the Land Office of Palembang considered bad. It was because the Land Office of Palembang had not provided consumer satisfaction in obtaining land certificate. Assessment of poor quality of service was gained in accordance with negative scores obtained from four dimensions of service quality, only one dimension had a positive score that was the dimension of direct evidence.